Achieving across-laboratory replicability in psychophysical scaling - Ward, Lawrence M.; Baumann, Michael; Moffat, Graeme; Roberts, Larry E.; Mori, Shuji; Rutledge-Taylor, Matthew; West, Robert L. (Frontiers in Psychology, 2015)
It is well known that, although psychophysical scaling produces good qualitative agreement between experiments, precise quantitative agreement between experimental results, such as that routinely achieved in physics or biology, is rarely or never attained. A particularly galling example of this is the fact that power function exponents for the same psychological continuum, measured in different laboratories but ostensibly using the same scaling method, magnitude estimation, can vary by a factor of three. Constrained scaling, in which observers first learn a standardized meaning for a set of numerical responses relative to a standard sensory continuum and then make magnitude judgments of other sensations using the learned response scale, has produced excellent quantitative agreement between individual observers’ psychophysical functions. Theoretically it could do the same for across-laboratory comparisons, although this needs to be tested directly. We compared nine different experiments from four different laboratories as an example of the level of across-experiment and across-laboratory agreement achievable using constrained scaling. In general, we found across-experiment and across-laboratory agreement using constrained scaling to be significantly superior to that typically obtained with conventional magnitude estimation techniques, although some of its potential remains to be realized.